Adults with Comorbid Posttraumatic Stress Disorder, Alcohol Use Disorder, and Opioid Use Disorder: The Effectiveness of Modified Prolonged Exposure - Peck, Kelly R.; Schumacher, Julie A.; Stasiewicz, Paul R.; Coffey, Scott F. (Journal of traumatic stress, 2018)
Opioid use disorders (OUDs) are a growing problem in the United States. When OUDs co‐occur with problematic drinking and posttraumatic stress disorder (PTSD), negative drug‐related mental and physical health outcomes may be exacerbated. Thus, it is important to establish whether PTSD treatments with established efficacy for dually diagnosed individuals also demonstrate efficacy in individuals who engage in problematic drinking and concurrent opioid misuse. Adults who met DSM‐IV‐TR criteria for PTSD and alcohol dependence were recruited from a substance use treatment facility and were randomly assigned to receive either modified prolonged exposure (mPE) therapy for PTSD or a non‐trauma‐focused comparison treatment. Compared to adults in a non‐OUD comparison group (n = 74), adults with OUD (n = 52) were younger, reported more cravings for alcohol, were more likely to use amphetamines and sedatives, were hospitalized more frequently for drug‐ and alcohol‐related problems, and suffered from more severe PTSD symptomatology, depressive symptoms, and anxiety, standardized mean differences = 0.36–1.81. For participants with OUD, mPE was associated with large reductions in PTSD symptomatology, sleep disturbances, and symptoms of anxiety and depression, ds = 1.08–2.56. Moreover, participants with OUD reported decreases in alcohol cravings that were significantly greater than those reported by the non‐OUD comparison group, F(1, 71.42) = 6.37, p = .014. Overall, our findings support the efficacy of mPE for PTSD among individuals who engage in problematic drinking and concurrent opioid misuse, despite severe baseline symptoms. Resumen Spanish s by the Asociación Chilena de Estrés Traumático (ACET) Adultos con Comorbidad de Trastorno de Estrés Postraumático, Trastorno por Consumo de Alcohol, y Trastorno por Consumo de Opiáceos: La Efectividad de una Exposición Prolongada Modificada EXPOSICION PROLONGADA PARA TEPT Y CONSUMO DE OPIACEOS Los trastornos por consumo de opiáceos (TCOs) son un creciente problema en los Estados Unidos. Cuando los TCOs co‐ocurren con consumo problemático de alcohol y trastorno de estrés traumático (TEPT), los resultados negativos en la salud física y mental como consecuencia de las drogas pueden exacerbarse. Así, es importante establecer si los tratamientos de TEPT con eficacia establecida para individuos diagnosticados dualmente también demuestran eficacia en individuos que presentan consumo problemático de alcohol y simultáneamente abuso de opiáceos. Los adultos que cumplieron con los criterios del Manual Diagnóstico y Estadístico de Trastornos Mentales (4ta Ed., texto revisado; Asociación Americana de Psiquiatría, 2000) para el TEPT y dependencia de alcohol fueron reclutados desde una dependencia de tratamiento de consumo de substancias y fueron asignados aleatoriamente a recibir terapia de exposición prolongada modificada (EPm) para TEPT, o a un tratamiento de comparación no focalizado en el trauma. En comparación con los adultos en un grupo de comparación sin TCO (n = 74), los adultos con TCO (n = 52) eran más jóvenes, reportaron más ansias de consumir alcohol, eran más propensos a usar anfetaminas y sedantes, estuvieron hospitalizados más frecuentemente por problemas asociados a drogas y alcohol, y sufrieron de sintomatología TEPT, síntomas depresivos, y ansiedad más severa (diferencias de medias estandarizadas = 0.36–1.81). Para los participantes con TCO, la EPm estuvo asociada con mayores reducciones en la sintomatología TEPT, trastornos del sueño, y síntomas de ansiedad y depresión, ds = 1.08–2.56. Además, los participantes con TCO reportaron disminución en el deseo de consumir alcohol que fue significativamente mayor en aquellas reportadas por el grupo de comparación sin TCO, F (1, 71.42) = 6.37, p = .014. En general, nuestros hallazgos apoyan la eficacia del EPm para TEPT entre individuos que presentan consumo problemático de alcohol y simultáneamente abuso de opiáceos, a pesar de la severidad de los síntomas iniciales (baseline en su acepción en inglés). 抽象 Traditional and Simplified Chinese s by AsianSTSS Adults with Comorbid Posttraumatic Stress Disorder, Alcohol Use Disorder, and Opioid Use Disorder: The Effectiveness of Modified Prolonged Exposure Traditional Chinese 標題: 創傷後壓力症、酒精使用失常和鴉片類藥物使用失常的成年共病患者: 長時間暴露療法 (修改版) 的效用 撮要: 鴉片類藥物使用失常(OUDs)在美國愈趨普遍。假如OUDs跟酗酒問題和創傷後壓力症(PTSD)同時發生, 與藥物相關的負面身心問題便有可能惡化。因此, 我們有必要了解對於同時有精神疾病及濫藥問題的患者已知有效的PTSD治療, 是否也對同時有酗酒問題和濫用鴉片類藥物的患者有效。我們從一個濫用藥物治療中心裡, 抽取符合《精神疾病診斷與統計手冊 (第四版) 》 (4th ed., text rev.; American Psychiatric Association, 2000)定義患PTSD和倚賴酒精的成人樣本, 把他們隨機分派到接受治療PTSD的長時間暴露療法 (修改版) (mPE)和非針對創傷的比較療法。與無OUD的成人比較樣本(n = 74)相比, 有OUD的成人 (n = 52)年紀較輕, 對酒精的慾望較大, 較高機會使用安非他命和鎮靜劑, 較常因藥物和酒精相關問題而入院, 亦有較嚴重的PTSD症狀學、抑鬱症狀、焦慮症(標準化平均數差異 = 0.36–1.81)。OUD的樣本裡, mPE跟PTSD症狀學、睡眠干擾、焦慮和抑鬱症狀大幅減弱有關(ds = 1.08–2.56)。此外, 有OUD的樣本與無OUD的比較組相比, 對酒精的慾望顯著較大幅地減弱(F(1, 71.42) = 6.37, p = .014)。整體結果證實, 對於同時有酗酒問題和濫用鴉片類藥物的PTSD患者, 即使其基線的症狀嚴重, mPE亦屬有效療法。 Simplified Chinese 标题: 创伤后压力症、酒精使用失常和鸦片类药物使用失常的成年共病患者: 长时间暴露疗法 (修改版) 的效用 撮要: 鸦片类药物使用失常(OUDs)在美国愈趋普遍。假如OUDs跟酗酒问题和创伤后压力症(PTSD)同时发生, 与药物相关的负面身心问题便有可能恶化。因此, 我们有必要了解对于同时有精神疾病及滥药问题的患者已知有效的PTSD治疗, 是否也对同时有酗酒问题和滥用鸦片类药物的患者有效。我们从一个滥用药物治疗中心里, 抽取符合《精神疾病诊断与统计手册 (第四版) 》 (4th ed., text rev.; American Psychiatric Association, 2000)定义患PTSD和倚赖酒精的成人样本, 把他们随机分派到接受治疗PTSD的长时间暴露疗法 (修改版) (mPE)和非针对创伤的比较疗法。与无OUD的成人比较样本(n = 74)相比, 有OUD的成人 (n = 52)年纪较轻, 对酒精的欲望较大, 较高机会使用安非他命和镇静剂, 较常因药物和酒精相关问题而入院, 亦有较严重的PTSD症状学、抑郁症状、焦虑症(标准化平均数差异 = 0.36–1.81)。OUD的样本里, mPE跟PTSD症状学、睡眠干扰、焦虑和抑郁症状大幅减弱有关(ds = 1.08–2.56)。此外, 有OUD的样本与无OUD的比较组相比, 对酒精的欲望显著较大幅地减弱(F(1, 71.42) = 6.37, p = .014)。整体结果证实, 对于同时有酗酒问题和滥用鸦片类药物的PTSD患者, 即使其基线的症状严重, mPE亦属有效疗法。